Effect of Thermomechanical Fermented Soybean Meal on Javanese Super Chicken’s Performance, Protease, and Blood Metabolic - Darmawan, Muhammad Arif; Saputro, Wahyu Subagio; Saraswati, Pramita Nindya; Setyono, Wahyu; Yano, Aan Andri; Akhirini, Novi; Suprayogi, Wara Pratitis Sabar (Faculty of Animal Science, Jenderal Soedirman University in associate with the Animal Scientist Society of Indonesia (ISPI) and the Indonesian Association of Nutrition and Feed Science (AINI), 2025)
Soybean meal, feedstuff obtained from soy seed oil extraction, is a common feed ingredient for poultry despite containing antinutritional factors (ANFs), which can alter digestive activity and decrease poultry productivity. ANFs are reportedly eliminable by fermentation protocol. This study identified the effect of thermomechanical Fermented Soybean Meal (FSBM) on Javanese Super Chicken’s protease activity, blood metabolism, and growth performance. A total of 90-day-old chicks (DOCs) of Indonesian male Javanese Super Chicken were allotted to three treatment groups: CON (non-FSBM); T1 (FSBM with Bacillus subtilis); T2 (FSBM with Aspergillus niger). All groups were replicated six times with five birds each. The study was conducted for 76 days, and all birds were healthy and vaccinated with Newcastle Diseases (ND), Lasota, and Gumboro A. The result indicated that thermomechanical FSBM affected significantly (P<0.05) daily feed intake, average daily gain, feed conversion ratio, total protein, total albumin, and globulin. Protease activity was not affected by the treatments.